The Influence of Family Friendly Policies and Technostress on Job Satisfaction in Mediation of Work Family Conflict and Work Family Benefits - Baiza, Ahmad; Hadi, Syamsul; Fadhillah, Muinah (Dinasti Publisher, 2024)
This research was conducted to analyze the influence of family friendly policies and technostress on job satisfaction. This research also aims to determine whether work family conflict and work family benefits mediate family friendly policies, technostress, and job satisfaction. Two factor theory as a framework in this research. The sampling technique method uses census sampling where the entire population is sampled, and the research subjects are employees at CV Rahmat Aulia. Sampling used a questionnaire from 122 respondents. Data analysis used inferential Partial Least Square (PLS), namely variance-based SEM, with SmartPLS software version 3.0. The research results show that family friendly policies and technostress have no effect on job satisfaction. Family friendly policies do not have a positive effect on job satisfaction, and technostress also does not have a negative effect on job satisfaction. The mediation results show that work family conflict and work family benefits mediate between family friendly policies and technostress on job satisfaction. Suggestions for further research are to expand the reach of research on similar companies in a particular area.